The Role of Interleukin-33 in Head and Neck Squamous Cell Carcinoma Is Determined by Its Cellular Sources in the Tumor Microenvironment - Peng, Liang; Sun, Wei; Chen, Lin; Wen, Wei-Ping (Frontiers in Oncology, 2021)
Objectives To investigate the role of interleukin-33 (IL-33) in head and neck squamous cell carcinoma (HNSCC). Materials and Methods RNA-seq data of 520 cases of HNSCC were retrieved from The Cancer Genome Atlas. The tumor microenvironment was deconstructed by xCell using bulk RNA-seq data. The cohort was dichotomized by the median IL-33 expression level. Immune cell components and molecular markers were compared between the high and low IL-33 groups. The prognostic value of IL-33 was evaluated by the log-rank test. Differential gene expression analysis and KEGG pathway enrichment analysis were also conducted. The relationship between the IL-33 expression level and the abundance of its potential cellular sources was evaluated by Pearson’s partial correlation test. Subgroup analysis was conducted in laryngeal, oropharyngeal, and oral cavity squamous cell carcinoma (LSCC, OPSCC, and OCSCC). Results The role of IL-33 in HNSCC was heterogeneous among tumors at different sites. In LSCC, IL-33 may increase the extent of malignancy of tumor cells and act as a pro-tumor factor. In OCSCC, IL-33 may play a role in orchestrating the immune responses against tumor cells and act as an antitumor factor. The role of IL-33 in OPSCC was undetermined. IL-33 in LSCC was mainly derived from endothelial cells, while IL-33 in OCSCC was mainly derived from endothelial and epithelial cells. Conclusion According to the different sources of IL-33 in LSCC and OCSCC, we propose a hypothesis that stroma-derived IL-33 could favor tumor progression, while epithelial-derived IL-33 could favor antitumor immune responses in HNSCC.